2021
DOI: 10.1002/cpt.2448
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐Based Pharmacokinetic and Drug–Drug Interaction Characterization of Antibody–Drug Conjugates in Oncology Clinical Development: An International Consortium for Innovation and Quality in Pharmaceutical Development Perspective

Abstract: Antibody-drug conjugates (ADCs) represent a rapidly evolving area of drug development and hold significant promise. To date, nine ADCs have been approved by the US Food and Drug Administration (FDA). These conjugates combine the target specificity of monoclonal antibodies with the anticancer activity of small-molecule therapeutics (also referred to as payload). Due to the complex structure, three analytes, namely ADC conjugate, total antibody, and unconjugated payload, are typically quantified during drug deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The analysis concluded that due to extremely low circulating levels of the unconjugated payloads following administration of ADCs the DI risk is low for these payloads to inhibit or induce CYP enzymes, UGTs, or transporters. The IQ ADC review article did not comment on the DI risk for proteins or payloads that are either pro‐inflammatory cytokines directly causing increases in cytokine levels, or that affect a disease state that may indirectly change pro‐inflammatory cytokine levels 54 . As discussed in the review articles by Li et al .…”
Section: Antibody–drug Conjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis concluded that due to extremely low circulating levels of the unconjugated payloads following administration of ADCs the DI risk is low for these payloads to inhibit or induce CYP enzymes, UGTs, or transporters. The IQ ADC review article did not comment on the DI risk for proteins or payloads that are either pro‐inflammatory cytokines directly causing increases in cytokine levels, or that affect a disease state that may indirectly change pro‐inflammatory cytokine levels 54 . As discussed in the review articles by Li et al .…”
Section: Antibody–drug Conjugatesmentioning
confidence: 99%
“…As discussed in the review articles by Li et al . and Boni et al 54,55 . many ADCs that are currently in development have moieties that could act as immune modulators.…”
Section: Antibody–drug Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is speculated that given the low systemic exposure, cytotoxic payload molecules are unlikely to cause clinically meaningful interactions but can be significantly affected by enzymes and transporters. Unique considerations may be needed when designing PK studies to evaluate interactions with cytotoxic payloads [45].…”
Section: Sgmentioning
confidence: 99%
“…(3) The complex payload release process in tumor including the bystander effect [ 146 ] makes it harder for PD modeling. (4) Each payload shows distinct PKPD profile that includes drug–drug interaction (DDI) [ 147 , 148 ]. With these complexities, modeling ADC PKPD has peculiar challenges while being an indispensable tool for ADC drug discovery and development.…”
Section: Prediction Of Human Pkpd Of Adc Using Mandsmentioning
confidence: 99%